A simple authentication encryption scheme. (2nd February 2017) - Mazumder, Rashed; Miyaji, Atsuko; Su, Chunhua
Summary: An authentication encryption (AE) scheme satisfies to transfer an authenticated data between 2 parties or more. There are vast applications of the AE such as access control, encryption, enhancing trust between multiple parties, and assure the originality of a message. However, the main challenge of the AE is to maintain low‐cost features for its construction. Furthermore, there is another emerging issue of Internet of Things (IoT) in the field of data and network communication. The numbers of application of the IoT are increasing expeditiously, where various kinds of device have been used such as IoT‐end device, constrained device, and RfID. Moreover, the main challenge of the IoT‐end devices and resource constrained devices is to keep a certain level of security bound including minimum cost. However, the IoT‐end devices, resource constrained devices, and RfID have lack of resources such as memory, power, and processors. Interestingly, the AE can play a vital role between data acquisition (sensors, actuators) and data aggregation of usual platform of the IoT. Thus, the construction of the AE should satisfy the properties of low‐cost, least resources, and less operating‐time. Though, there are many familiar constructions of AE such as OTR, McOE, POE, OAE, APE, COPE, CLOC, and SILK but most of the schemes depend on the features of nonce and associate data. In the aspect of security, the usage of nonce and associated data are adequate. However, these 2 features increase the overhead cost. Therefore, we propose a simple construction of IV‐based AE where blockcipher compression function is used as encryption function. Our proposed scheme's efficiency‐rate is 1 with reasonable privacy‐security bound. In addition, it can encrypt arbitrary length of message in each iteration without padding.